Experience Of Foreign Countries in The Integration of Sciences - Boboxonov Shohruh Usmonxon ugli (Zien Journals, 2024)
International cooperation in the field of science is a complex system that includes the interaction of scientists, organizations, a set of events and contacts of a scientific and diplomatic nature. The authors’ conclusions about international practices of internationalization and support of international competitiveness in science are based on analyzing the real-time data on publication activity, current strategic documents and programs for scientific development
Keywords: Experience; foreign countries; scientific development